Compact betatron with four controlling-field periodicity elements; Instruments and Experimental Techniques; Vol. 29, iss. 4, pt. 1 - Chakhlov V. L. Vladimir Lukianovich; Pushin V. S.; Burov G. I.; Zvontsov A. A. Aleksander Akimovich; Zvorygin V. P.; Zrelov Yu. D. (1986, 1986)
A compact 3-Mev betatron is described. The electromagnet of the betatron uses removable four-element poles, which form a magnetic field with azimuthal variation. The betatron accelerates 2 multiplied by (times) 10**1**0 particles per cycle. The cycle repetition frequency is up to 400 Hz. The radius of the equilibrium orbit is 4. 5 cm. The maximum interpole gap is 4 cm. The depth of magnetic-field variation on the equilibrium radius is 0. 15.